Managing the divide - Chaturvedi, Abha (Pune, 1985)
Interpreting industrial relations as co-opera tion within conflict and taking managements as the most dominant actors in the scene the present book analyses three major areas of industrial relations; industrial unionism, and humanisation of the work-place. peace, trade The first part analyses the trends in industrial confrontations in India, and emphasizes the need for shifting the focus from place to rela tions. The second part examines the trade union movement in India in the light of its present state and future challenges. sections explore the possibilities of building The last relations through removing the emotional' and 'psychological' sterility of the organisations. The precondition for such a change, according to the author, is a shift in the value paradigm of the work-designers and the work-design. The book will be of interest to all those who think about industrial relations or manage them.
Keywords: Industrial relations